Dose-response relationships of physical activity with bone mineral density and muscle mass in visceral obesity: A metabolic heterogeneity perspective. - Hongxin Zhuo; Xintao Zhang (PLoS ONE, 2025)
Background Obesity, particularly visceral adiposity, is associated with metabolic disorders and musculoskeletal deterioration. While physical activity (PA) benefits metabolic health, its dose-response effects on bone mineral density (BMD) and muscle mass in visceral obesity remain unclear. Objective This study investigated associations between PA levels and musculoskeletal outcomes in visceral obesity, considering metabolic heterogeneity. Methods Utilizing data from 3,077 visceral obesity participants (NHANES 2011-2018), PA levels were categorized as inactive (0 min/week), low- (1-150), moderate- (150-300), and high-active (>300). Weighted linear regression and restricted cubic splines analyzed associations, adjusted for demographic, socioeconomic, and health-related covariates. Subgroup analyses were conducted based on metabolic clusters, which were defined using k-means clustering according to blood pressure, visceral adiposity index, and HbA1c levels. Results High-active PA correlated with increased lumbar BMD (β = 0.239, 95%CI:0.055-0.424, P = 0.012), showing nonlinear saturation effects. Muscle mass improved dose-dependently with moderate-active (β: 0.021; 95%CI: 0.007-0.035; P = 0.005) and high-active (β:0.032; 95%CI: 0.018-0.046; P < 0.001). Subgroups with favorable metabolic profiles exhibited stronger PA-musculoskeletal benefits, while metabolic dysfunction attenuated these associations. Conclusions Bone adaptations require high-intensity PA thresholds, whereas muscle mass responds linearly to PA dose. Metabolic status modulates both relationships. Integrating metabolic optimization into exercise strategies is critical for improving musculoskeletal health in visceral obesity.